Pendekatan Hermeneutika dalam Pengkajian Islam - Hani Zahrani; Rubini (STAI Terpadu Yogyakarta, 2023)
There are contradictions in the science of Quranic interpretation in Islamic studies. In Indonesia, Adian Husaini opposes Hermeneutics in absolute terms, while M. Qurais Shihab argues that Hermeneutics can be used in interpreting the Qur'an. In Egypt, Hassan Hanafi considers hermeneutics to be applicable in religious texts, while Muhammad Imarah opposes it. Therefore, the hermeneutic approach in Islamic studies needs to be studied to expand knowledge and understanding of the text. This article discusses the definition, characteristics, principles, and role of Hermeneutics in Islamic studies through library research method. Hermeneutics is the interpretation of classical texts developed in various fields. International figures have emerged in Hermeneutics. In the Islamic context, hermeneutics can help interpret difficult-to-understand Quranic verses. With previous developments and evaluations, it is recommended to use Hermeneutics in the future to analyze modern-day texts in books, manuscripts, and news.